2021
DOI: 10.3389/fmed.2021.642723
|View full text |Cite
|
Sign up to set email alerts
|

Disparities of SARS-CoV-2 Nucleoprotein-Specific IgG in Healthcare Workers in East London, UK

Abstract: Introduction: SARS-CoV-2 antibody detection serves as an important diagnostic marker for past SARS-CoV-2 infection and is essential to determine the spread of COVID-19, monitor potential COVID-19 long-term effects, and to evaluate possible protection from reinfection. A study was conducted across three hospital sites in a large central London NHS Trust in the UK, to evaluate the prevalence and duration of SARS-CoV-2 IgG antibody positivity in healthcare workers.Methods: A matrix equivalence study consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…To date, both sero-epidemiological and targeted cohort studies from different countries have reported detectable levels of virus-specific antibodies and duration of the protective immune response from 3 to 13 months after infection [6,7,10,12,13,17,19,21,24,25]. Previous cohort studies on the formation and persistence of SARS-CoV-2-specific humoral immune response mainly included healthcare workers as a target group having the highest risk of being exposed to SARS-CoV-2 [13,14,16,19,20,24,26,27]. However, a long-term monitoring of antibody levels in naturally infected healthcare workers seems to be difficult or even impossible after the start of a global vaccination, as the healthcare sector is considered a priority group for vaccination in many countries [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, both sero-epidemiological and targeted cohort studies from different countries have reported detectable levels of virus-specific antibodies and duration of the protective immune response from 3 to 13 months after infection [6,7,10,12,13,17,19,21,24,25]. Previous cohort studies on the formation and persistence of SARS-CoV-2-specific humoral immune response mainly included healthcare workers as a target group having the highest risk of being exposed to SARS-CoV-2 [13,14,16,19,20,24,26,27]. However, a long-term monitoring of antibody levels in naturally infected healthcare workers seems to be difficult or even impossible after the start of a global vaccination, as the healthcare sector is considered a priority group for vaccination in many countries [28].…”
Section: Discussionmentioning
confidence: 99%
“…The cohort study conducted in the UK demonstrated that the levels of antibodies against the SARS-CoV-2 N protein declined by 31.3% over a period of 3 months [20]. In contrast, another cohort study of healthcare workers in the UK showed that the seropositivity against the SARS-CoV-2 S protein remained stable in 94% (95% credibility interval [CrI] 91-96%) of participants for 6 months [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high variability in the presence, titre and duration of specific antibodies has been reported (2)(3)(4), often positively correlating with disease severity (3)(4)(5). Some factors determining differences in clinical manifestations and humoral response, such as age, ethnicity and co-or pre-existing medical conditions have already been described (2,6). Underlying genetic and molecular determinants of humoral responses are currently being investigated with some promising results, although these studies mainly focussed on subjects experiencing severe COVID-19 (7)(8)(9).…”
Section: Introductionmentioning
confidence: 77%
“…SARS-CoV-2 infected subjects can display symptoms within a wide range of severity, from asymptomatic or pauci-symptomatic forms (characterised by fever, cough, fatigue, sore throat, loss of smell) to respiratory failure and systemic manifestations (sepsis, septic shock, and multiple organ dysfunction syndromes (1). Similarly, high variability in the presence, titre and duration of specific antibodies has been reported (2)(3)(4), often positively correlating with disease severity (3)(4)(5). Some factors determining differences in clinical manifestations and humoral response, such as age, ethnicity and co-or pre-existing medical conditions have already been described (2,6).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation